Study of the Adjuvant Properties of Chitosan in Complex with Recombinant Outer Membrane Protein F and Recombinant Toxoid Pseudomonas Aeruginosa - Kaloshin, A.A.; Mihailova, N.A. (Biomedical Chemistry: Research and Methods, 2025)
The aim of the study was to investigate adjuvant properties of chitosan in comparison with aluminum hydroxide during immunization with recombinant proteins of Pseudomonas aeruginosa. We used recombinant outer membrane protein F (OprF) and recombinant toxoid of P. aeruginosa, to which 0.5% chitosan preparation dissolved in glutamic acid with pH 5.0 or aluminum hydroxide gel were added. The ratios of aluminum hydroxide to protein of 3:1 and 1:1 were tested, and chitosan was added at 100 μg and 50 μg for one immunizing dose. The resulting preparations were administered to mice intraperitoneally twice with a two-week interval, and then two weeks later the animals were infected intraperitoneally with P. aeruginosa (PA-103). It was shown that double administration of the recombinant OprF protein at a dose of 25 μg and recombinant toxoid at a dose of 50 μg with both aluminum hydroxide and chitosan contributed to the development of equivalent protective properties. With the complex introduction of two recombinant proteins, an increase in protective properties was observed using both adjuvants. The possibility of using antigens without adjuvant and reducing their immunizing dose during booster immunization was investigated. It turned out that a two-fold reduction in the immunizing dose did not reduce the protective effect upon repeated administration, and in the case of chitosan, an increase in the immune response was observed during booster immunization with recombinant antigens without an adjuvant. Thus, for the recombinant proteins of P. aeruginosa, the adjuvant properties of chitosan were revealed. They are not inferior in the induction of protective properties to aluminum hydroxide.